History of discovery and study of new primary minerals at Jachymov - Veselovsky,F.; Ondrus,P.; Gabasova,A.; Hlousek,J.; Vlasimsky,P. (Journal of the Czech Geological Society, 2003)
Jachymov is the type locality for the following primary minerals: argentopyrite, krutovite, millerite, sternbergite, and uraninite. The history of their discovery is described in this contribution. The paper sums up the history of discovery of other type minerals at Jachymov [560].
Keywords: Jachymov; mineralogy; history of discovery